Hubungan Vertical Jump Dengan Jump Shoot Pada Permainan Bola Basket Grup Megic Kid Lubuklinggau - sepra winata, bimo sepra winata bimo; Suhdy, Muhammad; Syafutra, Wawan (Jurnal MensSana, 2023)
Abstract This study aims to determine whether there is a relationship between vertical jump and jump shoot in the basketball game of the megic kid Lubuklinggau group. The research method used is descriptive and the type of research is correlational analysis. The study population was the Magic Kid Lubuklinggau Putra group. The sample in this study was the Magic Kid Lubuklinggau Putra group as many as 10 people. The data collection technique in this study was a test. The data analysis technique used the following steps: normality test, homogeneity test and chorealisonal test. The instruments used in this study were the vertical jump test, and the jump shoot into the ring for 1 minute. The results of statistical analysis from multiple correlation analysis obtained an F-count of 0.1262, with a significance level of 5%, an F-table of 0.632 was obtained. It turns out that F-count 0.1262 is smaller than F-table 0.632, meaning that there is no significant relationship between vertical jump and jump shoot in basketball games. The results showed that there was no significant relationship between vertical jump and jump shoot in the basketball game of the megic kid Lubuklinggau group. Abstrak Penelitian ini bertujuan untuk mengetahui adakah hubungan antara vertikal jump dengan jump shoot pada permainan bola basket grup megic kid lubuklinggau. Metode penelitian yang digunakan deskriptif dan jenis peneltian adalah analisis korelasional. Populasi penelitian ini adalah grup magic kid lubuklinggau putra. Sampel pada penelitian ini adalah grup magic kid lubuklinggau putra sebanyak 10 orang. Teknik pengambilan data dalam penelitian ini dengan tes. Teknik analisis data dengan langah-langkah : uji normalitias, Uji homogenitas dan uji korealisonal. Instrumen yang digunakan dalam penelitian ini adalah tes vertical jump, dan jump shoot ke ring selama 1 menit. Hasil analisis statistika dari analisis korelasi ganda diperoleh R-hitung sebesar 0,13, dengan taraf signifikansi 5 %, berarti terdapat hubungan yang sangat rendah vertical jump dan jump shoot pada permainan bolabasket. Hasil penelitian menunjukkan tidak ada hubungan yang signifikan vertikal jump dengan jump shoot pada permainan bola basket grup megic kid lubuklinggau.